The Effect of Ethanol Extract of Yam Bulbs (Pachyrhizus Erosus L Urb) on the Growth of Staphylococcus Aureus Bacteria Agar Diffusion Method - Slamet (Jurnal teknologi Kesehatan Borneo, 2021)
Bengkuang Plant (Pachyrhizus erosus L. Urb) is a plant that can be used as herbal medicine. The community-made uses yam into powder by drying the place that is not exposed to direct sun, then pounded into a powder. This powdered yam is used by mixing clean water and used as powder. Bulbs are proven to contain flavonoid compounds, isoflavonoid, saponin, and daidzein, which can function as antibatter. The purpose of this study was to explain the concentration of tuber extract of ethanol tuber (Pachyrhizus erosus L. Urb) on the growth of Staphylococcus aureus bacteria with the agar diffusion method. The research design used in this research is quasi-experimental (Quasi-Experimental). The sample of this research is extract of bamboo tuber ethanol (Pachyrhizus erosus L. Urb) with concentration of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% and 90%. Based on the result of the research, the measurement of the inhibitory zone of Staphylococcus aureus bacteria was found to average 6,00 mm at a concentration of 10% -40%, 7.33 mm at concentration 50%, 7.67 mm at concentration 60%, 9.33 at concentration 70 %, 10.67 mm at concentrations of 80% and 13.33 mm at a concentration of 90%. The data were analyzed by Kendall's Tau test (p = 0,000 <0,05), so it can be concluded that there is an influence of extract of bamboo tuber ethanol (Pachyrhizus erosus L. Urb) on the growth of Staphylococcus aureus bacteria agar diffusion method.